CRITICAL HERMENEUTIC INTERPRETATION OF A CASE OF EDUCATIONAL REGULATIONS: The Spanish constitution of 1978 and the rupture of the “educational constitutional pact” - Camacho, Guillermo Miranda (2022)
This article is inserted within the framework of the critical theory of educationalnormative. It follows the methodology of a case study, adopting Jürgen habermas’smodel of repression of generalizable interests as a critical hermeneuticalinterpretation frame. The object of interpretation is the breakup of the constitutionaleducation pact, stipulated in Article 27 of the Spanish Constitution of 1978, with theapproval of the Law of the Statute of Educational Institutions (LOECE in Spanish).